Predicting the Ultimate Capacity of Frictional Jacked Concrete Piles Installed in Mixed Silty Sands in the Philippines - Buensuceso, Benjamin III (Philippine Engineering Journal, 2022)
Jacked piles have increasingly been used to support structural loads, though methods for ultimate axial capacity prediction and installation termination criteria remain relatively undeveloped compared to driven and bored piles. These methods were also primarily trained on databases from China and Hong Kong which have different soil conditions and pile jacking technology and methodology. This paper studies the utility of final jacking force (Pjack) readings as an estimate of the actual ultimate capacity of jacked frictional precast piles installed in 36 to 45 m of silty soils in the San Simon, Pampanga, Luzon region in the Philippines. The accuracy of existing capacity prediction methods are assessed vs. the well-established method of using capacity estimates from high-strain dynamic load tests (PDA tests). The ratios of PDA estimated capacities to final jacking forces during installation were an average of 3.58, much higher than empirically predicted ratios ranging from 1.12 to 1.59. This increase was attributed to the phenomenon of pile setup, though empirical pile setup formulas also significantly under-predicted the increase. This indicates existing pile jacking installation criteria and pile setup models may not be applicable for this pile and soil configuration.   Keywords: jacked piles; load test; PDA tests; pile foundations; pile setup